Los argumentos para la comprensión de Dios en Clemente de Alejandría: Influjos órficos en "Stromata V" - Calabrese, Claudio César, 1959-‏ (2019)
En el presente artículo examinamos la incorporación de textos órficos aplicados a la comprensión de Dios, según Clemente de Alejandría en Stromata V, dentro del proceso de recepción de la cultura helenística en la interpretación del dato revelado. Realizamos la exposición a partir del contexto cultural del helenismo y de su comprensión del cosmos y de lo divino y de la forma de interpretación alegórica del mito en los versos órficos.
In this article, we examine the incorporation of Orphic texts applied to the understanding of God according to Clement of Alexandria in Stromata V, within the process of receiving Hellenistic culture into the interpretation of the revealed data. Our explanation takes as its starting points the cultural context of Hellenism and its understanding of the cosmos and the divine as well as the form of allegorical interpretation of myth in Orphic verses. With philological method, we observe Clement’s mode of appropriation by differentiating the original quote in its context, the present context, and the hermeneutic intention.
Keywords: Clemente de Alejandría; Dios; Helenismo